Causal Relationships Between Modifiable Risk Factors of Cognitive Impairment, Cognitive Function, Self-Management, and Quality of Life in Patients With Rheumatic Diseases. (September 2018) - Park, JiSuk; Oh, HyunSoo; Park, Won; Kwon, SeongRyul; Ham, OkKyung; Suh, YeonOk; Jeong, HyeSun; Seo, WhaSook
Abstract : BACKGROUND: Rheumatic diseases are one of the most common types of chronic conditions that affect cognitive functions. PURPOSE: To develop and verify a hypothetical model of causal relationships between modifiable risk factors for cognitive impairment, cognitive function, self-management, and quality of life in patients with rheumatic diseases. METHODS: A hypothetical model was developed on the basis of empirical evidence. The fitness of the model was verified on 210 patients with rheumatic diseases. RESULTS: The prevalence of cognitive impairment was 49.0%. Smoking, underlying diseases, pain, and fatigue had a significant direct effect on cognitive impairment. Only cognitive impairment had a significant direct effect on self-management. Fatigue, anxiety, depression, and cognitive function had a significant direct effect on quality of life. CONCLUSIONS: The importance of proper management of symptoms and health habits should be emphasized to prevent and delay the progression of cognitive impairment and improve adherence to self-management regimens and quality of life.